2021
DOI: 10.1111/liv.14936
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen plasma transfusion in acute variceal haemorrhage: Results from a multicentre cohort study

Abstract: Background: Fresh frozen plasma (FFP) transfusion is often used in the management of acute variceal haemorrhage (AVH) despite best practice advice suggesting otherwise.Objective: We investigated if FFP transfusion affects clinical outcomes in AVH. Design, setting and patients:We performed a retrospective cohort study of 244 consecutive, eligible patients admitted to five tertiary health care centres between 2013 and 2018 with AVH.Main outcome measurements: Multivariable regression analyses were used to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Administration of plasma to correct coagulopathy in cirrhosis with bleeding is a very common practice [25]; however, this practice not only is ineffective, but is also likely harmful [26]. In a recent, multicenter cohort study administration of fresh frozen plasma in cirrhosis with VH was independently associated with increased risks of 42-day mortality (primary outcome, OR: 9.41, 95% CI: 3.71-23.90), failure to control bleeding at five days (OR: 3.87, 95% CI: 1.28-11.70) and length of stay (adjusted OR: 1.88, 95% CI: 1.03-3.42) (secondary outcomes) [27]. No specific data exist regarding the management of severe thrombocytopenia in the setting of VH, and therefore, no recommendation can be made.…”
Section: Additional Measures No Need For Correction Of Coagulopathymentioning
confidence: 99%
“…Administration of plasma to correct coagulopathy in cirrhosis with bleeding is a very common practice [25]; however, this practice not only is ineffective, but is also likely harmful [26]. In a recent, multicenter cohort study administration of fresh frozen plasma in cirrhosis with VH was independently associated with increased risks of 42-day mortality (primary outcome, OR: 9.41, 95% CI: 3.71-23.90), failure to control bleeding at five days (OR: 3.87, 95% CI: 1.28-11.70) and length of stay (adjusted OR: 1.88, 95% CI: 1.03-3.42) (secondary outcomes) [27]. No specific data exist regarding the management of severe thrombocytopenia in the setting of VH, and therefore, no recommendation can be made.…”
Section: Additional Measures No Need For Correction Of Coagulopathymentioning
confidence: 99%
“…43 Finally, a retrospective multicenter study evaluating the use of FFP in management of acute variceal bleeding reported increased mortality and 5-day rebleeding risk in those who received FFP after adjustment for confounders. 44 There are increasing guidance documents from expert societies recommending against the prophylactic use of FFP in the periprocedural setting (Table 2) irrespective of procedural bleeding risk.…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
“…Furthermore, therapeutic transfusions of FFP have been shown to significantly increase portal pressures and may thereby paradoxically increase bleeding risk (e.g., in EVL) 43 . Finally, a retrospective multicenter study evaluating the use of FFP in management of acute variceal bleeding reported increased mortality and 5‐day rebleeding risk in those who received FFP after adjustment for confounders 44 …”
Section: Benefits/risks Of Interventions To Address Coagulation In Th...mentioning
confidence: 99%
“…Results from a multicenter cohort study," the authors describe increased mortality at 42 days in patients transfused with fresh frozen plasma (FFP) for acute variceal hemorrhage. 1 Within the FFP-transfused group, variceal bleeding was the leading cause of mortality, and the authors report that most deaths were related to worsening portal hypertension. They further describe that patients transfused additional units of FFP had significantly higher odds ratio of failure to control bleeding at 5 days and hospital length of stay (LOS) >7 days, with a 26% increased risk of failure to control bleeding with each additional unit of FFP.…”
Section: Observed Incidence Of Hypofibrinogenemia In Cirrhotic Patientsmentioning
confidence: 99%
“…We read with interest, recently published article in this journal titled “Fresh frozen plasma transfusion in acute variceal hemorrhage: Results from a multicenter cohort study,” the authors describe increased mortality at 42 days in patients transfused with fresh frozen plasma (FFP) for acute variceal hemorrhage 1 . Within the FFP‐transfused group, variceal bleeding was the leading cause of mortality, and the authors report that most deaths were related to worsening portal hypertension.…”
Section: Fibrinogen (Mg/dl) Inr N Median (Range) Iqr Mean Sdmentioning
confidence: 99%